2018
DOI: 10.3389/fcimb.2017.00531
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cysteine Desulfidase CdsB Involved in Releasing Cysteine Repression of Toxin Synthesis in Clostridium difficile

Abstract: Clostridium difficile, a major cause of nosocomial diarrhea and pseudomembranous colitis, still poses serious health-care challenges. The expression of its two main virulence factors, TcdA and TcdB, is reportedly repressed by cysteine, but molecular mechanism remains unclear. The cysteine desulfidase CdsB affects the virulence and infection progresses of some bacteria. The C. difficile strain 630 genome encodes a homolog of CdsB, and in the present study, we analyzed its role in C. difficile 630Δerm by constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…6a) strongly affects production of toxins in these species [38,39]. Recent studies have shown that σ 54 and CdsR mediate the cysteine-dependent repression of toxin production in C. difficile [40,41]. We identified a putative σ 54 promoter and UAS site of CsdR upstream of cdsB gene involved in cysteine catabolism in C. difficile, C. botulinum, C. sporogenes, and C. scatologenes ( Fig.…”
Section: Regulation Of the Stickland Reactionsmentioning
confidence: 88%
“…6a) strongly affects production of toxins in these species [38,39]. Recent studies have shown that σ 54 and CdsR mediate the cysteine-dependent repression of toxin production in C. difficile [40,41]. We identified a putative σ 54 promoter and UAS site of CsdR upstream of cdsB gene involved in cysteine catabolism in C. difficile, C. botulinum, C. sporogenes, and C. scatologenes ( Fig.…”
Section: Regulation Of the Stickland Reactionsmentioning
confidence: 88%
“…These results are not surprising since most of the genes transcribed by RNAP associated to SigL respond to specific inducers through their associated EBP activators sensing these signals (Francke et al, 2011;Nie et al, 2019). For example, cysteine or proline strongly induces the expression of cdsB and prdC genes and the prdA operon, respectively, in a CdsR-or a PrdR-dependent manner (Bouillaut et al, 2013;Gu et al, 2017). We did not detect a SigL-dependent control of cdsB expression as previously observed (Gu et al, 2017) and only a two-fold decrease of expression was detected for three genes of the prdA operon in the sigL::erm mutant ( Supplementary Table S7).…”
Section: Sigl-mediated Control Of Gene Expression In C Difficilementioning
confidence: 99%
“…Interestingly, the genes for 24 transcriptional activators (named EBP for enhancer binding proteins activating SigLdependent promoters) containing a AAA + domain, which is responsible for ATP hydrolysis and their interaction with SigL (Francke et al, 2011), are present in the genome of C. difficile. Only two EBPs, CsdR and PrdR, controlling cysteine and proline catabolism, respectively, have been experimentally characterized in C. difficile (Bouillaut et al, 2013;Gu et al, 2017;Gu et al, 2018). By combining in silico analysis, RNA-seq and genomewide promoter mapping, we have recently identified more than 200 non-coding RNAs (ncRNAs) in C. difficile from different functional classes including riboswitches, transand cis-acting antisense RNAs (Soutourina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations